Influence of Bi-7 Day Reverse Repo Rate, Gross Domestic Product (GDP), and Industrial Production Index (IPI) on Corporate Sukuk Growth in Indonesia with Inflation as Moderating Variable in 2011-2021 - Ayu Dwi Astuti; Anton Bawono (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The development of corporate Sukuk, which is relatively small compared to thedevelopment of state Sukuk, is the background of this research. This study aims to determine whether there is an effect of the bi-7 day reverse repo rate, gross domestic product, and industrial production index on the growth of corporate Sukuk with inflation as the moderating variable in 2011-2021. This research is a quantitative study with a sample of 44 data in Indonesia for the 2011-2021 period, the results of which are published by OJK, BPS, and BI. The data is processed by software eviews 10. The data analysis tool used is Multiple Analysis and Moderated Regression Analysis (MRA), with instrument tests including Stationary Test and Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test). After the classical assumption test was carried out, multicollinearity symptoms were detected in this study, so to cure these symptoms the researchers removed several variables from the equation model. This is done to obtain a good equation and not bias multicollinearity. With the remaining variables in the regression model, the results of the research show that the bi-7 day reverses repo rate (X1) has a negative and insignificant effect on the growth of corporate Sukuk, and the Industrial Production Index (X3) has a positive and significant effect on the growth of corporate Sukuk, inflation can moderate the effect bi-7 day reverserepo rate and Gross Domestic Product on corporate Sukuk growth (X1*Z and X2*Z).